Financial Performance Analysis of PT XYZ and Compliance Of Financial Loan Covenant Toward Debt Repayment Capability - Azizah, Adinda Nur; Sutardi, Acip (Integrasi Sains Media, 2023)
In 2022, PT XYZ faced a decline in net sales of -16.42%. At the same time, Indonesia's furniture industry also faced a decline in export value. This research analyses PT XYZ's financial performance from 2018 to 2022, specifically regarding its debt repayment capability. Financial ratios from several aspects, such as profitability, liquidity, activity, and solvency ratios, will be generated to reflect the firm's performance and trend in the past five years. Other than evaluating the firm's financial ratios, this research will also evaluate the firm's compliance with financial loan covenants in existing bank loans and bond issuance. From the financial ratio analysis, the firm's performance plummeted in 2022, mainly due to the decline in sales experienced by PT XYZ. There may be some issues regarding the firm's liquidity performance. However, it can be seen from the solvency ratios such as DSCR and Interest Coverage Ratio that the firm can still meet its obligations in paying its debt interest and principal payments. Compliance with financial loan covenants indicates a covenant breach in the debt-to-EBITDA ratio, which is applied as a financial loan covenant by Bank DEF and Bank JKL. However, the firm can still pay its debt principal and even pay off the credit facilities. The research found that the decline in sales faced by the firm significantly impacted the firm's weakened financial performance in 2022. Regarding compliance with financial loan covenants from bank loans and bond issuance, the covenant breach does not affect the firm's capability in debt repayments.